2018
DOI: 10.1029/2018gl080187
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Stable Holocene Basin‐Scale Overturning Circulation Despite Variable Currents Along the Deep Western Boundary of the North Atlantic Ocean

Abstract: While substantial changes in thermohaline circulation related to deglacial climate variability are well established, the role of this circulation in Holocene climate variability remains uncertain. Here we use two dynamical proxies, 231Pa/230Th ratios and mean sortable silt size ( trueSS¯), to reconstruct Holocene bottom water circulation at the intermediate‐depth Carolina Slope. We find no substantial change in deep current speed or 231Pa export at this site during the Holocene, suggesting consistent 231Pa exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 58 publications
(138 reference statements)
4
22
0
1
Order By: Relevance
“…Over 50 years' (1966–2019) worth of data have been compiled to create the global thorium database ( n = 1,167) presented here (Adkins et al, ; Anderson et al, , Anderson et al, , Anderson et al, , Anderson et al, ; Bausch, ; Böhm et al, ; Bohrmann, ; Borole, ; Bradtmiller et al, , , ; Broecker, ; Broecker et al, ; Brunelle et al, , ; Causse & Hillaire‐Marcel, ; Chase et al, , ; Chong et al, ; Costa, McManus, & Anderson, ; Costa & McManus, ; Crusius et al, ; Dekov, ; Denis et al, ; Dezileau et al, , ; Durand et al, ; Fagel et al, ; Francois et al, , Francois et al, ; Frank, Eisenhauer, Bonn, et al, , Frank, Eisenhauer, Kubik, et al, , ; Fukuda et al, ; Galbraith et al, ; Geibert et al, ; Gherardi et al, , ; Gottschalk et al, ; Hickey, ; Hillaire‐Marcel et al, ; Hoffmann et al, , ; Jaccard et al, , ; Jacobel et al, ; Jonkers et al, ; Kienast et al, ; Ku & Broecker, ; Kumar et al, ; Lam et al, ; Lamy et al, ; Lao et al, ; Lippold et al, , Lippold et al, , Lippold et al, , Lippold et al, ; Loubere et al, ; Loveley et al, ; Lund et al, ; Mangini & Dominik, ; Marcantonio et al, , Marcantonio et al, ...…”
Section: Background: the Marine Geochemistry Of 230thunclassified
See 1 more Smart Citation
“…Over 50 years' (1966–2019) worth of data have been compiled to create the global thorium database ( n = 1,167) presented here (Adkins et al, ; Anderson et al, , Anderson et al, , Anderson et al, , Anderson et al, ; Bausch, ; Böhm et al, ; Bohrmann, ; Borole, ; Bradtmiller et al, , , ; Broecker, ; Broecker et al, ; Brunelle et al, , ; Causse & Hillaire‐Marcel, ; Chase et al, , ; Chong et al, ; Costa, McManus, & Anderson, ; Costa & McManus, ; Crusius et al, ; Dekov, ; Denis et al, ; Dezileau et al, , ; Durand et al, ; Fagel et al, ; Francois et al, , Francois et al, ; Frank, Eisenhauer, Bonn, et al, , Frank, Eisenhauer, Kubik, et al, , ; Fukuda et al, ; Galbraith et al, ; Geibert et al, ; Gherardi et al, , ; Gottschalk et al, ; Hickey, ; Hillaire‐Marcel et al, ; Hoffmann et al, , ; Jaccard et al, , ; Jacobel et al, ; Jonkers et al, ; Kienast et al, ; Ku & Broecker, ; Kumar et al, ; Lam et al, ; Lamy et al, ; Lao et al, ; Lippold et al, , Lippold et al, , Lippold et al, , Lippold et al, ; Loubere et al, ; Loveley et al, ; Lund et al, ; Mangini & Dominik, ; Marcantonio et al, , Marcantonio et al, ...…”
Section: Background: the Marine Geochemistry Of 230thunclassified
“…Over 50 years ' (1966-2019) worth of data have been compiled to create the global thorium database (n = 1,167) presented here (Adkins et al, 2006;Anderson et al, 2006Bausch, 2018;Böhm et al, 2015;Bohrmann, 2013;Borole, 1993;Bradtmiller et al, 2006Bradtmiller et al, , 2007Bradtmiller et al, , 2009Broecker, 2008;Broecker et al, 1993;Brunelle et al, 2007Brunelle et al, , 2010Causse & Hillaire-Marcel, 1989;Chase et al, 2003Chase et al, , 2014Chong et al, 2016;Costa, McManus, & Anderson, 2017;Crusius et al, 2004;Dekov, 1994;Denis et al, 2009;Dezileau et al, 2000Dezileau et al, , 2004Durand et al, 2017;Fagel et al, 2002;Francois et al, 1990, Francois et al, 1993Frank, Eisenhauer, Bonn, et al, 1995Fukuda et al, 2013;Galbraith et al, 2007;Geibert et al, 2005;Gherardi et al, 2005Gherardi et al, , 2009Gottschalk et al, 2016;Hickey, 2010;Hillaire-Marcel et al, 2017;Hoffmann et al, 2013Hoffmann et al, , 2018Jaccard et al, 2009Jaccard et al, , 2013…”
Section: Data Compilationmentioning
confidence: 99%
“…Here we aim at reconstructing large-scale AMOC variability for the Holocene, combining high-resolution 231 Pa/ 230 Th, εNd, and δ 13 C records with existing data from Bermuda Rise sediments, which sensitively recorded past changes in AMOC dynamics (Böhm et al, 2015;Deaney et al, 2017;Gutjahr & Lippold, 2011;Henry et al, 2016;Keigwin & Boyle, 2000;McManus et al, 2004;Rempfer et al, 2017;Roberts et al, 2010). Existing Holocene data sets from this area are not available in sufficient temporal resolution or have been obtained from potentially less sensitive locations, hindering identification of short-scale AMOC oscillations (Hoffmann et al, 2018;Lippold et al, 2016;McManus et al, 2004;Ng et al, 2018;Rempfer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using the 231 Pa/ 230 Th proxy have concluded that a strong circulation of the North Atlantic prevailed during the Holocene (Hoffmann et al, 2018) and pronounced weakenings of AMOC strengths occurred during past cold phases (Bradtmiller et al, 2014;Gherardi et al, 2009;Lippold et al, 2016; Figure 1. Overview map of the northwest Atlantic.…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies using the 231 Pa/ 230 Th proxy have concluded that a strong circulation of the North Atlantic prevailed during the Holocene (Hoffmann et al, ) and pronounced weakenings of AMOC strengths occurred during past cold phases (Bradtmiller et al, ; Gherardi et al, ; Lippold et al, ; McManus et al, ; Ng et al, ). Nevertheless, a clear picture of the vertical structure of the deglacial circulation and the evolution of AMOC is still lacking, in particular due to insufficient spatial and temporal proxy coverage.…”
Section: Introductionmentioning
confidence: 99%